The corrosion properties of multilayer coatings deposited on stainless steel and Ti4Al6V substrates - Zykova, A.; Safonov, V.; Walkowich, J.; Rogowska, R.; Yakovin, S. (Вопросы атомной науки и техники, 2009)
Stainless steel (SS), titanium (Ti) and its alloys are the most widely used for clinical applications. The surface modification of metals with ceramic coatings by means of modern plasma methods is perspective way to reduce corrosion, to achieve better biocompatibility and to improve the performance of medical devices. The comparative analysis of the TiN, ZrO₂, Al₂O₃ and multilayer nitride/oxide coatings adhesion properties, hardness, elastic modulus, thickness, and corrosion resistance parameters at 05 N NaCl and SBF solution was made.